PENGEMBANGAN SOAL TERBUKA UNTUK MENJELAJAHI KREATIVITAS MATEMATIKA SISWA DALAM MATERI GAMBAR DUA DIMENSI - Rachmadina Eka Herdianti; Muhammad Baidawi; Fitria Khasanah (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2023)
This research is motivated by the importance of developing a pedagogical orientation that focuses on non-routine problem-solving skills and exploring students' creative thinking in mathematics learning. The primary focus of the study is the development of open-ended questions and testing their effectiveness in mapping the hierarchy of students' mathematical creativity in two-dimensional geometry. Using the Borg and Gall Research and Development (R&D) method, this research combines quantitative and qualitative data collection. The trial subjects involved 30 students of grade VII-D at SMP Negeri 1 Jabung, Malang, Indonesia, using open-ended test sheets, response questionnaires, and documentation. The research findings indicate that the product's feasibility validation by experts achieved a score of 79.4 percent, which qualifies as good. Product effectiveness parameters were also optimally met, based on the average score of 3.8 on the student feedback questionnaire and 3.5 on the observational assessment of original class activities. The main conclusion confirms that the developed open-ended question draft is valid and effective in exploring the diversity of students' mathematical creativity levels independently. This tool successfully triggered indicators of fluency, flexibility, and strategic novelty by modifying rectangular shading into various geometric visual scenarios. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya pengembangan orientasi pedagogik yang berfokus pada kecakapan pemecahan masalah non-rutin dan eksplorasi berpikir kreatif peserta didik dalam pembelajaran matematika. Fokus utama kajian diarahkan pada pengembangan soal terbuka (open-ended) serta pengujian tingkat efektivitasnya dalam memetakan hierarki kreativitas matematika siswa pada materi geometri bangun datar dua dimensi. Menggunakan metode Research and Development (R&D) model Borg dan Gall, riset ini mengombinasikan pengumpulan data kuantitatif serta kualitatif. Subjek uji coba melibatkan 30 peserta didik kelas VII-D SMP Negeri 1 Jabung, Malang, Indonesia, dengan instrumen berupa lembar tes terbuka, kuesioner respon, dan dokumentasi. Temuan penelitian menunjukkan hasil validasi kelayakan produk oleh para ahli mencapai persentase skor 79,4 persen yang termasuk dalam kualifikasi kategori baik. Parameter efektivitas produk juga terpenuhi secara optimal berdasarkan perolehan rata-rata skor kuesioner tanggapan balik siswa sebesar 3,8 dan penilaian observasi aktivitas orisinal kelas sebesar 3,5. Simpulan utama menegaskan bahwa draf soal terbuka yang dikembangkan valid dan efektif mengeksplorasi keberagaman level kreativitas matematika siswa secara mandiri. Perangkat ini sukses memicu kemunculan indikator kelancaran, fleksibilitas, hingga kebaruan strategi melalui modifikasi bentuk arsir persegi panjang menjadi skenario visual geometri yang bervariasi.